Застосування альдегідів фуранового ряду у мультикомпонентних реакціях - Вахула, Андрій Романович (Львівський національний університет імені Івана Франка, 2019)
Дисертація присвячена розробці способів одержання гетероциклів різних класів з арилфурановими фрагментами мультикомпонентними реакціями, використовуючи як вихідні реагенти 5-арилфурфуроли і 3-(5-арил-2-фурил)акролеїни, та вивченню властивостей одержаних сполук. Розширено межі застосування реакції Радзішевського (одержання полізаміщених імідазолів з арилфурановим фрагментом), Ганча (синтез заміщених 4-(5-арил-2-фурил)- 1,4-дигідропіридинів), Біджинеллі (синтез 4-[5-арил-2-фурил]-2-ксо(тіоксо)-1,2,3,4- тетрагідропіримідинів), Ґрьобке (одержання похідних імідазо[2,1-b][1,3,4]тіадіазолу та імідазо[2,1-b]тіазолу), Угі–Дільса-Альдера (взаємодія ізонітрилу з ненасиченою кислотою, аміном (ароматичним або аліфатичним) та 3-(5-арил-2-фурил)акролеїнами). Досліджено взаємодію заміщених 5-арилфуран-2-карбальдегідів з димедоном та 6-аміноурацилом і одержано конденсовані гетероцикли – 5-(5-арил-2-фурил)-5,8,9,10-тетрагідропіримідо[4,5-b]хінолін-2,4,6-тріони. З’ясовано, що 5-арилфуран-2-карбальдегіди реагують з подвійним надлишком димедону та ацетатом амонію з утворенням 3,3,6,6-тетраметил-9-(5-арил-2-фурил)-3,4,6,7,9,10-гексагідроакридин-1,8(2Н,5Н)-діонів. Розроблено спосіб синтезу 4,6-дизаміщених 2-аміно-3-ціанопіридинів чотирикомпонентною циклізацією – 5-арилфурфуролу, ароматичного кетону, малонодинітрилу і ацетату амонію. Показано, що 5-арилфурфуроли можна застосовувати для конструювання 2-аміно-7,7-диметил-5-оксо-4-(5-арил-2-фуран)-5,6,7,8-тетрагідро-4Н-хромен-3-карбонітрилів. Застосовуючи трикомпонентну циклізацію, розроблено способи синтезу похідних 7-аміно-5-[5-арил-2-фурил]-3,4- дигідро-1H-ізотіохромен-6,8-дикарбонітрил-2,2-діоксидів. Як реагенти використали альдегіди арилфуранового ряду, динітрил малонової кислоти та 3-оксотетрагідро-2H-тіопіран-1,1-діоксид. Розроблено загальну методику конструювання гібридних структур з фрагментами тіазоло[3,2-b][1,2,4]триазол-6-онів та імідазо[2,1-b][1,3]тіазол-3-онів трикомпонентною реакцією 5-арилфурфуролів чи 3-(5-арил-2-фурил)акролеїнів з хлороцтовою кислотою та меркаптоазолами. Деякі синтезовані 3,3,6,6-тетраметил-9-[5-(арил-2-фурил)]-3,4,6,7,9,10-гексагідро-акридин-1,8(2Н,5Н)-діони виявляють люмінесценцію, а 2-(5-арил-2-фурил)-4,5-дифеніл-1Н-імідазоли – практично корисні для органічної електроніки фотофізичні властивості. The scientific work is devoted to the development of new approaches to synthesis of heterocycles with arylfuran moieties. For this purpose 5-arylfuran-2-carbaldehydes and 3-(5- aryl-2-furyl)acroleins were used as starting reagents in multicomponent transformations. One of the fundamental problems of organic chemistry is the development of effective original methods for the synthesis of new heterocyclic compounds. Since most drugs belong to heterocycles, such studies also have practical implications. Of particular interest are synthetic approaches based on readily available starting compounds. It is scientifically grounded and practically expedient to search for one-pot methods for the synthesis of polycyclic compounds through multicomponent reactions. The rise of multicomponent reactions chemistry in recent times is an important part of scientific research and practical application in the field of organic synthesis, since they save resources and promote the introduction of the concept of "green" chemistry. The development of multicomponent reactions for the synthesis of heterocycles with pharmacophore fragments is aimed at solving this fundamental problem. In the course of scientific work, a number of previously unknown compounds were obtained. 5-Arylfuran-2-carbaldehydes and 3-(5-aryl-2-furyl)acroleins were used in a number of multicomponent reactions for the first time. The limits of the application of: the Radziszewski reaction (preparation of 2,4,5-triarylimidazoles with an arylfuran moiety), Hantzsch reaction (synthesis of substituted 4-(5-aryl-2-furyl)-1,4-dihydropyridines), Biginelli reaction (synthesis of 4-[5-(aryl-2-furyl]-2-oxo(thioxo)-1,2,3,4-tetrahydropyrimidines), Groebke reaction (preparation of imidazo[2,1-b][1,3,4]thiadiazole and imidazo[2,1-b]thiazolederivatives), Ugi–Diels-Alder reaction (interaction of isonitrile with unsaturated acid, amines (aromatic or aliphatic) and 3-(5-aryl-2-furyl)acroleins) were disclosed. Reaction of substituted 5-arylfuran-2-carbaldehydes with dimedone and 6-aminouracil has been studied and as a result 5-(5-aryl-2-furyl)-5,8,9,10-tetrahydropyrimido[4,5-b]quinoline-2,4,6-trions have been obtained. It has been established that 5-arylfuran-2-carbaldehydes reacts with a double excess of dimedone and ammonium acetate to form 3,3,6,6-tetramethyl-9-(5-aryl-2-furyl)-3,4,6,7,9,10-hexahydroacridine-1,8-(2H,5H)-diones. A method for the synthesis of 4,6-disubstituted 2-amino-3-cyanopyridines by four-component cyclization (5-arylfurfurals, aromatic ketone, malonodinitrile and ammonium acetate) has been developed. It has been shown that 5-arylfurfurals can be used in design of 2-amino-7,7-dimethyl-5-oxo-4-(5-aryl-2-furyl)-5,6,7,8-tetrahydro-4H-chromen-3-carbonitriles. Using three-component cyclization, methods for the synthesis of 7-amino-5-[5-aryl-2-furyl]-3,4-dihydro-1H-isothiochromene-6,8-dicarbonitrile-2,2-dioxides derivatives have been developed. In this transformation 5-arylfurfurals, malonodinitrile and 3-oxotetrahydro-2H-thiopyran-1,1-dioxide were used as reagents. A general approach for design of hybrid structures with fragments of thiazolo[3,2-b][1,2,4]triazol-6-ones and imidazo[2,1-b][1,3]thiazol-3-ones has been developed. For this purpose three-component reactions of 5-arylfuran-2-carbaldehydes or 3-(5-aryl-2-furyl)acroleins with chloroacetic acid and mercaptoazoles were used. Some of the synthesized 3,3,6,6-tetramethyl-9-[5-(aryl-2-furyl)]-3,4,6,7,9,10-hexahydro-acridine-1,8-(2H,5H)-diones showed strong luminescence, and 2-(5-aryl-2-furyl)-4,5-diphenyl-1H-imidazoles exhibit photophysical properties that are practically useful for applications in organic electronics. Thus, methods for obtaining a number of new heterocyclic compounds with arylfuran moieties and compounds with new heterocyclic ensembles have been developed. Диссертация посвящена разработке способов получения гетероциклов различных классов с арилфурановыми фрагментами мультикомпонентными реакциями, используя в качестве исходных реагентов 5-арилфурфуролы и 3-(5-арил-2-фурил)акролеины, а также изучению свойств полученных соединений. Расширены границы применения реакции Радзишевского (получение полизамещенных имидазолов с арилфурановыми фрагментами), Ганча (синтез замещенных 4-(5-арил-2-фурил)-1,4-дигидропиридинов), Биджинелли (синтез 4-[5-арил-2-фурил]-2-оксо(тиоксо)-1,2,3,4-тетрагидропиримидинов), Ґрѐбке (получение производных имидазо[2,1-b][1,3,4]тиадиазола и имидазо[2,1-b]тиазола), Уги–Дильса-Альдера (взаимодействие изонитрила с ненасыщенной кислотой, амином (ароматическим или алифатическим) и 3-(5-арил-2-фурил)акролеином). Исследовано взаимодействие замещенных 5-арилфуран-2-карбальдегидов с димедоном и 6-аминоурацилом и получены конденсированные гетероциклы – 5-(5-арил-2-фурил)-5,8,9,10-тетрагидропиримидо[4,5-b]хинолин-2,4,6-трионы. Установлено, что 5-арилфуран-2-карбальдегиды реагируют с двойным избытком димедона и ацетатом аммония с образованием 3,3,6,6-тетраметил-9-(5-арил-2-фурил)-3,4,6,7,9,10-гексагидроакридин-1,8-(2Н,5Н)-дионов. Разработан способ синтеза 4,6-дизамещенных 2-амино-3-цианопиридинов четырехкомпонентной циклизацией – 5-арилфурфуролa, ароматического кетона, малонодинитрила и ацетата аммония. Показано, что 5-арилфурфуролы можно применять для конструирования 2-амино-7,7-диметил- 5-оксо-4-(5-арил-2-фурил)-5,6,7,8-тетрагидро-4Н-хромен-3-карбонитрилов. Применяя трехкомпонентную циклизацию, разработаны способы синтеза производных 7-амино-5-[5-арил-2-фурил]-3,4-дигидро-1H-изотиохромен-6,8-дикарбонитрил-2,2-диоксидов. В качестве реагентов использовали альдегиды арилфуранового ряда, малонодинитрил и 3-оксотетрагидро-2H-тиопиран-1,1-диоксид. Разработана общая методика конструирования гибридных структур с фрагментами тиазоло[3,2-b][1,2,4] триазол-6-онов и имидазо[2,1-b][1,3]тиазол-3-онов трехкомпонентной реакцией 5-арилфурфуролов или 3-(5-арил-2-фурил)акролеинов с хлоруксусной кислотой и меркаптоазолами. Некоторые из синтезированных 3,3,6,6-тетраметил-9-[5-(арил-2-фурил)]-3,4,6,7,9,10-гексагидроакридин-1,8-(2Н,5Н)-дионов проявляют люминесценцию, а 2-(5-арил-2-фурил)-4,5-дифенил-1H-имидазолы – практически полезные для органической электроники фотофизические свойства.
Application of aldehydes of the furan series in multicomponent reactions
Применение альдегидов фуранового ряда в мультикомпонентных реакциях
Keywords: мультикомпонентні реакції; 5-арилфурфуроли; 3-(5-арил-2- фурил)акролеїни; гетероциклізації; циклоприєднання; multicomponent reactions; 5-arylfuran-2-carbaldehydes; 3-(5-aryl-2- furyl)acroleins; heterocyclization; cycloaddition; мультикомпонентные реакции; 5-арилфурфуролы; 3-(5-арил-2- фурил)акролеины; гетероциклизации; циклоприсоединение; 547.7+547.72